Naturally‐occurring dietary salicylates in the genesis of functional gastrointestinal symptoms in patients with irritable bowel syndrome: Pilot study. Issue 8 (21st July 2021) - Tuck, Caroline J; Malakar, Sreepurna; Barrett, Jacqueline S; Muir, Jane G; Gibson, Peter R
Abstract: Background and Aim: An elimination‐rechallenge dietary approach targeting naturally‐occurring bioactive chemicals has been proposed to alleviate functional gastrointestinal symptoms. A major focus of this approach is salicylates. This study aimed to address the potential role of dietary salicylates in the induction of symptoms in patients with irritable bowel syndrome (IBS). Methods: A pilot, double‐blind, randomized, cross‐over trial of 2‐week low‐ versus high‐salicylate diets (6.6 and 27.9 g/day salicylate, respectively) was undertaken. All foods were provided containing minimal quantities of other potential food triggers. Gastrointestinal and extraintestinal symptoms were measured daily using a 100‐mm visual‐analogue‐scale. Results: Ten participants with IBS completed the study, including one with known aspirin‐sensitivity. Overall, no differences in symptoms were observed ( P = 0.625; Friedman test). However, clear symptom provocation was seen in the aspirin‐sensitive participant, with all abdominal symptoms and tiredness worsening during the high‐salicylate diet. A similar trend was seen in another participant, where abdominal symptoms gradually worsened during the high‐salicylate diet. Conclusions: These results provide some evidence that food‐related salicylates may influence the genesis of symptoms in a subset of patients with IBS. A larger cohort is needed to determine the incidence of salicylate‐sensitivity and further evaluate the diet as a potential therapeutic target. The protocol was registered at www.anzctr.org.au (ACTRN12620001250921). Abstract : This pilot randomised controlled trial (RCT) provides valuable data regarding the potential use of a diet low in naturally‐occurring dietary salicylates to reduce symptoms associated with common conditions such as irritable bowel syndrome.